(untitled) (Journal of Foreign Language Studies, 2019)
Nowadays, active learning is used in education systems of many developed countries. It puts an emphasis on learners’ acquisition and learning process rather than outcomes, facilitate their development of individual thinking, self-study and problem-solving skills. This paper presents an experimental study on adopting this approach in “Japanese for tourism” classes at the Japanese Department, Hanoi University. It points out the remaining problems of traditional teaching methods, advantages and challenges of this approach; thence, provides instructions as to effectively use and assess it to improve teaching.